As faces do amor em Otelo The faces of love in Othello - Maria Zaira Turchi (Signótica, 2010)
O artigo analisa como em Otelo, de Shakespeare, as relações entre amor, sexualidade, casamento representam o centro da investigação da tragédia, num conflito que envolve amor espiritual e amor carnal – processo de idealização e de degradação. The article analyses how in Shakespeare’s play Othello the relations among love, sexuality, marriage represent the heart of the tragedy, in a conflict that envolves spiritual love and sexual love – idealization and degradation.